Aortic wall shear stress in Marfan syndrome. Issue 4 (20th November 2012) - Geiger, Julia; Arnold, Raoul; Herzer, Lena; Hirtler, Daniel; Stankovic, Zoran; Russe, Max; Langer, Mathias; Markl, Michael
<x xml:space="preserve">Abstract</x> The aim of this study was to quantify changes in thoracic aortic wall shear stress (WSS) in asymptomatic patients with Marfan syndrome (MFS) compared with healthy controls. WSS in the thoracic aorta was quantified based on time‐resolved 3D phase contrast MRI with three‐directional velocity encoding (4D flow MRI, temporal resolution ∼44 ms, spatial resolution ∼2.5 mm) in 24 patients with confirmed MFS (age = 18 ± 12 years) and in 12 older healthy volunteers (age = 25 ± 3 years). Diameters of the thoracic aorta normalized to body surface area were similar for both groups. Peak systolic velocity, absolute WSS, time‐averaged WSS, circumferential WSS, peak systolic WSS, and WSS eccentricity were calculated in eight analysis planes distributed along the thoracic aorta. Plane‐wise comparison revealed significant differences between MFS patients and volunteers in the proximal ascending aorta for peak systolic velocities (1.11 ± 0.23 m/s vs. 1.34 ± 0.18 m/s, P = 0.004) and circumferential WSS (0.14 ± 0.03 N/m2 vs. 0.11 ± 0.02 N/m2, P = 0.007). WSS eccentricity was altered in most of the ascending aorta and proximal arch (P = 0.009–0.020). MFS patients demonstrated segmental differences in peak systolic WSS with a significantly higher WSS at the inner curvature in the proximal ascending aorta and at the anterior part in the more distal ascending aorta (P < 0.01). These findings indicate differences in WSS associated with MFS despite similar aortic dimensions compared to controls. Magn Reson Med, 70:1137–1144, 2013. © 2012 Wiley Periodicals, Inc.